Identification of Five Ferroptosis-Related LncRNAs as Novel Prognosis and Diagnosis Signatures for Renal Cancer - Shu, Xiangjun; Zhang, Zaiqi; Yao, Zhi-Yong; Xing, Xiao-Liang (Frontiers in Molecular Biosciences, 2022)
Background: Ferroptosis is a novel regulated cell death that is characterized by iron-dependent oxidative damage. Renal cancer is the second most common cancer of the urinary system which is highly correlated with iron metabolism. The aim of our present study was to identify suitable ferroptosis related prognosis signatures for renal cancer. Methods: We downloaded the RNA-seq counts data of renal cancer from the cancer genome atlas dababase, used the DESeq2, Survival, Cox regression analyses to screen the prognosis signatures. Results: We identified 5 ferroptosis related differentially expressed lncRNAs (DOCK8-AS1, SNHG17, RUSC1-AS1, LINC02609, and LUCAT1) were independently correlated with the overall survival (OS) of patients with renal cancer. The risk assessment model and diagnosis model constructed by those 5 FR-DELs could well predict the outcome and the diagnosis of renal cancer. Conclusion: Our present study not only suggested those 5 FR-DELs could be used as prognosis and diagnosis signatures for renal cancer, but also provided strategies for other cancers in screening of ferroptosis related biomarkers.